2021
DOI: 10.1039/d0qm00825g
|View full text |Cite
|
Sign up to set email alerts
|

Review on new horizons of aggregation induced emission: from design to development

Abstract: An unusual behavior of some organic luminophores is known as Aggregation Induced Emission (AIE). The exposure of this concept to the scientific community significantly changes the perception towards conventionally used...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(14 citation statements)
references
References 150 publications
0
14
0
Order By: Relevance
“…Whereas the fluorescence property of conformationally restricted, planar, conjugated molecules has been known for many years, the aggregation-induced emission enhancement (AIEE) exhibited by conformationally flexible conjugated systems is a more recent phenomenon . TPE ( 1 ) and its substituted variants are widely used as fluorescence probes by exploiting their AIEE, which is theorized to result from a restriction in conformational freedom upon aggregation .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the fluorescence property of conformationally restricted, planar, conjugated molecules has been known for many years, the aggregation-induced emission enhancement (AIEE) exhibited by conformationally flexible conjugated systems is a more recent phenomenon . TPE ( 1 ) and its substituted variants are widely used as fluorescence probes by exploiting their AIEE, which is theorized to result from a restriction in conformational freedom upon aggregation .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Established conjugated systems based upon a tetrasubstituted CC core are tetraphenylethylene TPE 1 , tetravinylethylene TVE 2 , and tetraethynylethylene TEE 3 (Figure , top right). All have been shown to have useful applications: in the case of TPE, as a fluorescence-based sensor by exploiting its aggregation-induced emission enhancement (AIEE) and in OLEDs; with TVE 2 due to its ability to rapidly generate structural complexity through pericyclic reaction sequences; and with TEE 3 through contributions in the field of molecular electronics . The properties of these molecules are determined not only by the connectivity of their π-frameworks but also by their conformational behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In the last couple of years, extensive research has been devoted to the development of exciting new generations of AIE materials. , These include, for instance, water-soluble AIE materials such as polymers or multifunctional charged AIEgen (poly)­electrolytes. , It has been clearly demonstrated that due to the combination of their size, special chemistry, and chromophore characteristics, these novel materials are superior compared to the individual small AIE analogs in terms of luminescence efficiency, photostability, low background signals, high resistance to photobleaching, structural diversity, etc. A very recent hot example shown in Figure is related to the observation of the 3D reconstruction and in situ crack tracing of polydimethylsiloxane/montmorillonite nanocomposite layers.…”
Section: Discussionmentioning
confidence: 99%
“…We believe this to be a significant advancement over the currently known examples of TADF AIE/CIE materials. 45 Furthermore, this work serves as a proofof-concept for a new simple one-step method for producing luminescent nanocrystals through use of sonication.…”
Section: Introductionmentioning
confidence: 99%